2010
DOI: 10.2214/ajr.09.3956
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Source Dual-Energy CT With Additional Tin Filtration: Dose and Image Quality Evaluation in Phantoms and In Vivo

Abstract: Purpose-To investigate the effect on radiation dose and image quality of the use of additional spectral filtration for dual-energy CT (DECT) imaging using dual-source CT (DSCT).Materials and Methods-A commercial DSCT scanner was modified by adding tin filtration to the high-kV tube, and radiation output and noise measured in water phantoms. Dose values for equivalent image noise were compared among DE-modes with and without tin filtration and singleenergy (SE) mode. To evaluate DECT material discrimination, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(126 citation statements)
references
References 42 publications
5
119
0
1
Order By: Relevance
“…The most recent technical advances include the ability of performing highpitch acquisitions of the entire chest in less than 1 s. Our study confirms that this approach results in good diagnostic image quality when applied for pulmonary CTA. DECT has been shown to provide simultaneous information on the presence of endoluminal thrombus and lung perfusion impairment [10][11][12][13][14][15]. Our study indicates that all CTA approaches tested result in good diagnostic image quality thus extending previous data [11].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The most recent technical advances include the ability of performing highpitch acquisitions of the entire chest in less than 1 s. Our study confirms that this approach results in good diagnostic image quality when applied for pulmonary CTA. DECT has been shown to provide simultaneous information on the presence of endoluminal thrombus and lung perfusion impairment [10][11][12][13][14][15]. Our study indicates that all CTA approaches tested result in good diagnostic image quality thus extending previous data [11].…”
Section: Discussionsupporting
confidence: 78%
“…DECT uses two different tube energies (kV) and allows analyses of the chemical composition of tissues by means of dual-energy data acquisition according to the material decomposition theory [8,9]. Previous studies have shown the potential of pulmonary blood volume maps obtained by DECT for showing perfusion impairment [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to subtraction of some stone signal from the stone periphery along with the iodine signal. In addition, the difference in collimation between dual-energy (1.2 mm) and single-energy (0.6 mm) acquisitions determines a relatively lower z-axis resolution that does not allow separation of the small stones and iodine in the urinary tract because of the volume averaging [41][42][43]. Similar results have been reported by reconstructing virtual unenhanced images from synchronous nephrographic/excretory enhancement (split-bolus CT urography technique) dualenergy CT images [44].…”
Section: Spectral Ct: Study Protocols and Clinical Applicationssupporting
confidence: 55%
“…Due to an energy spectra overlap between 100 and 140 kVp, these scanners had to be operated at 80 and 140 kVp, resulting in the inability to be used in the abdomen due to a low penetration depth and beam-hardening artifact [40,41].…”
Section: Spectral Ct: Study Protocols and Clinical Applicationsmentioning
confidence: 99%
“…8,54 For both DECT-DS and DECT-SW, the xray exposure from both tubes matched that of a single-source CT protocol, with the dose ratio of the low-and high-energy spectra was 19:1. By performing the experiment, this ratio was chosen empirically to maximize the discrimination performance of DECT.…”
Section: Ct Systems For Comparisonmentioning
confidence: 97%